Молекулярно-радиационная теория фотонной, диффузионной и электронной теплопроводности - Никитенко, Н.И. (Видавничий дім "Академперіодика" НАН України, 2009)
Наведено аналiтичнi вирази для електронної, фотонної i дифузiйної теплопровiдностi залежно вiд температури, густини i мiкроскопiчних характеристик середовищ. Одержано температурну залежнiсть густини вiльних електронiв у провiдниках. Подано результати зiставлення теоретичних i експериментальних даних. Analytic expressions for electronic, photonic, and diffusive heat conductivities depending on the temperature, density, and microscopic characteristics of the environment are given. The temperature dependence of the density of free electrons in conductors is obtained. The results of the comparison of theoretical and experimental data are presented.